2020
DOI: 10.1302/2633-1462.19.bjo-2020-0130.r1
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid injections during the COVID-19 pandemic

Abstract: Aims To describe the incidence of adverse clinical outcomes related to COVID-19 infection following corticosteroid injections (CSI) during the COVID-19 pandemic. To describe the incidence of positive SARS-CoV-2 reverse transcriptase polymerase chain reaction (RT-PCR) testing, positive SARS-COV2 IgG antibody testing or positive imaging findings following CSI at our institution during the COVID-19 pandemic. Methods A retrospective observational study was undertaken of consecutive patients who had CSI in our loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 21 publications
(18 reference statements)
2
27
0
1
Order By: Relevance
“…However, short‐term or low‐dose steroids such as is indicated for delayed‐type hypersensitivity can be safely used 37 . In patients without a known positive test result for SARS‐CoV‐2, there appears to be no increased risk of contracting the virus even in the presence of comorbidities for which steroids are frequently used 38,39 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, short‐term or low‐dose steroids such as is indicated for delayed‐type hypersensitivity can be safely used 37 . In patients without a known positive test result for SARS‐CoV‐2, there appears to be no increased risk of contracting the virus even in the presence of comorbidities for which steroids are frequently used 38,39 …”
Section: Discussionmentioning
confidence: 99%
“…37 In patients without a known positive test result for SARS-CoV-2, there appears to be no increased risk of contracting the virus even in the presence of comorbidities for which steroids are frequently used. 38,39 The patient in this report had already recovered from confirmed SARS-CoV-2 infection, and as such treatment with steroid would be appropriate in any case had she required its use.…”
Section: Managementmentioning
confidence: 91%
“…A larger study with 504 steroid injections had a 2.7% rate of infection, of which 1.1% were asymptomatic. There were no severe adverse outcomes to COVID-19 infection reported in the study [ 14 ]. Compared to our study, where we have zero infection rates, the rate of infection of COVID-19 is still low with no severe adverse outcomes following steroid injection.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Chang et al reported no significant elevation in the risk of developing COVID-19 infection following steroid injection compared to the general population [ 13 ]. McKean et al also demonstrate a low incidence of COVID-19 following corticosteroid injection with no major adverse outcomes [ 14 ]. We hypothesize that there will be a very low risk of developing COVID-19 infection following musculoskeletal steroid injection.…”
Section: Introductionmentioning
confidence: 99%
“…Corticosteroid injections are routinely used for the localised management of a broad range of painful musculoskeletal conditions, with the knee and shoulder being the two most common areas injected. 1 , 2 , 3 The injection is predominantly given to patients suffering from joint arthritis, bursitis, tendinopathy, and synovitis. 1 , 2 The objective is to control pain, improve the quality of activities of daily living, increase range of motion, and in some instances it may also delay or prevent surgery.…”
Section: Introductionmentioning
confidence: 99%